How air pollution fuels respiratory infections in children: current insights - Susanna Esposito; Valentina Fainardi; Annachiara Titolo; Angela Lazzara; Marialaura Menzella; Beatrice Campana; Alberto Argentiero; Nicola Principi (Frontiers in Public Health)
BackgroundAir pollution is a significant global health concern, particularly for younger children who are especially susceptible to its adverse effects. Pollutants such as particulate matter (PM), nitrogen oxides (NO and NO₂), sulfur dioxide (SO2), ozone (O3), and carbon monoxide (CO) are associated with increased risks of upper respiratory tract infections (URTI) and lower respiratory tract infections (LRTI). While this association is well-documented, there are critical gaps in understanding the magnitude of these risks, the roles of specific pollutants, and the influence of age, sex, and exposure duration.MethodsTo confirm the relationship between air pollution and respiratory tract infections in children and to identify areas for further research on reducing pollution-related respiratory damage, a literature review was conducted using the MEDLINE/PubMed database for studies published from January 2000 to December 2024. Eligible studies included randomized controlled trials, cohort studies, and meta-analyses focusing on the relationship between air pollution and respiratory infections in children. Studies were grouped by pollutant type, exposure timing, and infection type.ResultsThe literature analysis confirmed that pollution significantly increases the risk of URTI and LRTI in children, with infants and young children being the most vulnerable. Potential mechanisms for the development of respiratory tract pollution-related diseases include the promotion of oxidative stress, induction of inflammatory responses, deregulation of the immune system, and genetic alterations. Prenatal exposure significantly alters respiratory tract development, increasing the risk of LRTI and acute otitis media (AOM) early in life. Both short-term and long-term postnatal exposures can cause severe and recurrent LRTIs, reducing quality of life and leading to frequent hospitalizations and early death. However, the available data do not allow for precise definition of the magnitude of the risk, the individual and combined roles of specific pollutants, and the influence of factors such as age, sex, duration, and site of exposure on the development and severity of respiratory infections. Inconsistent findings on pollutant combinations and specific diseases like otitis media highlight the need for further research.ConclusionAir pollution is a major risk factor for respiratory infections in children, both prenatal and postnatal exposure can have significant negative impact. However, present knowledge is inadequate to develop effective preventive and therapeutic measures. Further studies are needed to minimize these cultural limits. In particular, it is necessary to delve deeper into how the various pollutants circulate, how they interact with each other, and how they are influenced by climate change and other environmental drivers. Results of these key researches can be translate into clinical and public health practice capable to help protect and improve children’s environmental health.